1980
DOI: 10.1111/j.1533-8525.1980.tb00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Religious Transmission Versus Religious Formation: Preadolescent-Parent Interaction

Abstract: Religiousness on the part of youth can result from transmission across generations and it can stem from a nurturant parent-child relationship. Interaction could occur between these variables. These relationships were tested using data from 2724 adolescents in grades 4-8 in intact families in southern Minnesota. The dependent measure involves five items measuring religious attendance, belief, and devotional practice. Both parental religiousness and support were significant predictors of preadolescent religiousn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Previous research has shown that the optimal conditions of religious transmission are parental nurturance, acceptance, support, and close relationship (Litchfield et al, 1997;Nelsen, 1980;Ozorak, 1989;Thomas, 1988;Wan-Ning et al, 1999). Family conflict, on the other hand, either between parent and child or between the spouses, has been shown to inhibit transmission of religious values (Clark and Worthington, 1987).…”
Section: Intergenerational Transmission Of Religion By Maternal Mdd Smentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research has shown that the optimal conditions of religious transmission are parental nurturance, acceptance, support, and close relationship (Litchfield et al, 1997;Nelsen, 1980;Ozorak, 1989;Thomas, 1988;Wan-Ning et al, 1999). Family conflict, on the other hand, either between parent and child or between the spouses, has been shown to inhibit transmission of religious values (Clark and Worthington, 1987).…”
Section: Intergenerational Transmission Of Religion By Maternal Mdd Smentioning
confidence: 94%
“…Children who reported their parents (who were religious) to be more nurturing were more religious on dimensions of attendance, belief, and devotional practice (Nelsen, 1980). Maternal transmission of religiousness (church attendance, religious denomination, and the concept of G-d) is greater when the adolescent perceives the parent as accepting and supportive (Wan-Ning et al, 1999).…”
Section: Conditions Associated With Transmission Of Religiositymentioning
confidence: 96%
“…The first group of studies explored the religious attitudes and practices of parents alongside those of their offspring (Acock & Bengston, 1978, 1980Clark, Worthington, & Danser, 1988;Dudley & Dudley, 1986;Hoge et al, 1982;Kieren & Munro, 1987). The second group of studies explored the religious attitudes and practices of the younger generation alongside their perceptions of parental religiosity (De Hart, 1990;De Vaus, 1983;Erickson, 1992;Francis & Brown, 1991;Hoge & Petrillo, 1978;Nelsen, 1980Nelsen, , 1981Ozorak, 1989).…”
mentioning
confidence: 99%
“…Abban a kérdésben azonban, hogy ez az együttjárás mennyire szoros és milyen tényezők befolyásolják az erősségét, nincsen konszenzus a kutatók körében. A család típusának és a szülők nevelési módszereinek szignifikáns hatásait egyes esetekben sikerült kimutatni (Myers 1996), míg máskor ez a tényező nem bizonyult meghatározónak (Nelsen 1980). A magyar társadalom olyan sajátosságait figyelembe véve, mint a házasságon belüli vallási homogámia vagy a földrajzi mobilitás alacsony szintje, előzetesen azt feltételeztük, hogy kutatásunk során szignifikáns kapcsolatot fogunk találni a szülők és gyermekeik vallásossága között.…”
Section: A Vallás öRöklődéseunclassified